Hubungan Helicopter Parenting dengan Anxiety Pada Remaja Akhir - Rusdi, Ahmad Hanafi; Trihandayani, Dewi; Sani, Muhammad Abdul Halim (Innovative: Journal Of Social Science Research, 2024)
Helicopter parenting is the involvement of parents in their children. For example, interfering in the child's affairs, making decisions for the child and staying away from obstacles faced by the child, so that the child finds it difficult to face everything in his life because the parents interfere too much in his life so that the child becomes a child who is not independent. Students with helicopter parenting have lower levels of happiness and are more likely to use drugs, antidepressants, or medication to reduce anxiety. Anxiety is a condition of feeling worried and feeling that something bad will happen. Apart from that, anxiety is a mixture of emotions that occurs when someone feels emotionally stressed or experiences internal conflict. This research aims to determine whether there is a relationship between helicopter parenting and anxiety in late adolescents. This research uses the Helicopter Parenting Instrument (HPI) measurement tool developed by Odenweller et all (2014) to measure helicopter parenting patterns and the Depression Anxiety Stress Scales (DASS) developed by P. F. Lovibond and S. H. Lovibond (1995) to measure anxiety. The results of this research show that there is a relationship between Helicopter Parenting and Anxiety of 0.256 < 0.05, which means there is a positive relationship between Helicopter Parenting and Anxiety. The sample used in this research was 236 respondents who were late teenagers. Consisting of 236 students aged 18-21 years, 78 were male and 158 were female.